Prognostic model of pain syndrome of temporomandibular joint dysfunction in patients with occlusion-articulation disorders - Proshchenko, Andriy (Journal of Education, Health and Sport, 2024)
Resume. Diagnostic efficiency and treatment of TMJ dysfunction was and remains an important problem modern dentistry. The urgency of this problem is determined by the great the prevalence of this pathology, the annual increase in the number of patient appeals, variety of clinical manifestations, significant difficulties in diagnosis and treatment. The aim of the work was to predict the pain syndrome of functional disorders of the masticatory apparatus when planning orthopedic treatment. Research materials and methods. Clinical and laboratory examination and orthopedic treatment of 150 patients with various variants of occlusal disorders were carried out, in 90 of them functional disorders of the masticatory apparatus were not accompanied by pain syndrome (comparison group), in 60 patients (main group) - TMJ dysfunction with pain syndrome Research results. The statistically significant data obtained by us demonstrate that the multi-level mechanism of changes in microarchitectonics due to occlusal and articulatory disorders, the influence of gender and age, and other unmodified factor balance of the work of muscle-articular structures of the dento-maxillary system can clinically manifest as a pain syndrome, and therefore requires orthopedic treatment taking into account correction of intra-articular disorders. Conclusions. Multivariate analysis of the cumulative effect of factors on the risk of pain syndrome development of functional disorders of the masticatory apparatus in case of violation of occlusal-articulatory relations allowed to create a prognostic model (model sensitivity - 0.967%, specificity - 0.971%) with a Youden index of 1.0. This prognostic model can serve as an accurate tool for the development of TMJ dysfunction pain syndrome at the stage of orthopedic treatment planning.